Sistem Pakar Diagnosa Penyakit Autoimun Menggunakan Metode Classical Probability - Muhammad Yunus Lubis (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
The expert system for diagnosing autoimmune diseases is a computer-based system that is used as a tool to diagnose autoimmune diseases based on a dynamic knowledge base. Autoimmune disease is a disease that attacks the human immune system which is generally common in women. Autoimmune is a disorder of the immune system due to the failure of the defense of the body's stability. This autoimmune disease causes harm to human organs because it can damage the organs of cells that are still healthy in a person's body. In this case the role of the computer is needed to provide information quickly, precisely, and accurately. One of them is the development of an expert system (Expert System) which is a new breakthrough in the computer world. Expert System is a computer application that provides services for consulting and obtaining solutions to a problem, which works like an expert. This study uses the Classical Probability method which is one method to prove whether a fact is certain or uncertain in the form of a metric that is usually used in expert systems, this study aims to build an application using the Classical Probability method by using the Dreamweaver application as a tool to diagnose autoimmune disease. By making this expert system, it is hoped that it will be useful for many people and can know clearly about Autoimmune disease from its symptoms and solutions, which are displayed in the form of a website using PHP programming with a MySQL database